Systematic review of outcome domains and instruments used in clinical trials of tinnitus treatments in adults. Issue 1 (December 2016) - Hall, Deborah; Haider, Haula; Szczepek, Agnieszka; Lau, Pia; Rabau, Sarah; Jones-Diette, Julie; Londero, Alain; Edvall, Niklas; Cederroth, Christopher; Mielczarek, Marzena; Fuller, Thomas; Batuecas-Caletrio, Angel; et al.
Abstract Background There is no evidence-based guidance to facilitate design decisions for confirmatory trials or systematic reviews investigating treatment efficacy for adults with tinnitus. This systematic review therefore seeks to ascertain the current status of trial designs by identifying and evaluating the reporting of outcome domains and instruments in the treatment of adults with tinnitus. Methods Records were identified by searching PubMed, EMBASE CINAHL, EBSCO, and CENTRAL clinical trial registries (ClinicalTrials.gov, ISRCTN, ICTRP) and the Cochrane Database of Systematic Reviews. Eligible records were those published from 1 July 2006 to 12 March 2015. Included studies were those reporting adults aged 18 years or older who reported tinnitus as a primary complaint, and who were enrolled into a randomised controlled trial, a before and after study, a non-randomised controlled trial, a case-controlled study or a cohort study, and written in English. Studies with fewer than 20 participants were excluded. Results Two hundred and twenty-eight studies were included. Thirty-five different primary outcome domains were identified spanning seven categories (tinnitus percept, impact of tinnitus, co-occurring complaints, quality of life, body structures and function, treatment-related outcomes and unclear or not specified). Over half the studies (55 %) did not clearly define the complaint of interest. Tinnitus loudness was the domain most often reported (14 %), followed by tinnitus distress (7 %). Seventy-eight different primary outcome instruments were identified. Instruments assessing multiple attributes of the impact of tinnitus were most common (34 %). Overall, 24 different patient-reported tools were used, predominantly the Tinnitus Handicap Inventory (15 %). Loudness was measured in diverse ways including a numerical rating scale (8 %), loudness matching (4 %), minimum masking level (1 %) and loudness discomfort level (1 %). Ten percent of studies did not clearly report the instrument used. Conclusions Our findings indicate poor appreciation of the basic principles of good trial design, particularly the importance of specifyingwhat aspect of therapeutic benefit is the main outcome. No single outcome was reported in all studies and there was a broad diversity of outcome instruments. PROSPERO registration The systematic review protocol is registered on PROSPERO (International Prospective Register of Systematic Reviews):CRD42015017525 . Registered on 12 March 2015 revised on 15 March 2016.